Effect of maximal training load on minerals and choline esterase concentrations as indicators to peripheral fatigue in wrestlers - Sabry Mohamed, E.; Abd El-Salam Akar, S. (World Journal of Sport Sciences, 2010)
Minerals play a major role in performance level. This research aims at identifying the effect of maximal training load on concentrations of some minerals (calcium, sodium and potassium) and Colin Esterase as indicators of fatigue in wrestlers. The researchers used the quasi-experimental approach with one group (pre-/post- measurement). Sample was chosen purposefully from junior wrestlers of Al-Shoban Al-Muslimin sports club in Ismailia, registered in the Egyptian wrestling federation under 15 years (8 wrestlers). Results showed that there was an effect of maximal training load on the concentrations of calcium, sodium and potassium and an increase of Colin Esterase as an indicator of peripheral fatigue in wrestlers.